Evaluation of Cardiac Function in Arabian Horses using Ultrasound (Journal of Hama University, 2019)
Echocardiography has become routinely the used procedure in the diagnosis, management, and following-up of patients with heart diseases. Echocardiography and intra-cardiac dimensions have not previously been reported in Arabian horses.The objective of this study was to measure cardiac dimensions; LVIDd, LVIDs, IVSd, IVSs, LVFWd, LVFWs in addition to determining cardiac function; Fractional Shortening (FS%) and Ejection Fraction (EF%) in Arabian horses.Echocardiography was performed at rest, on /36/ Arabian horses aged from /5/ to /13/ years old with body weight: /332 ± 12/ kg, and free of cardiac disease. We used of ultrasound scanner NOVEKO "AMIB7v" with electronic micro convex probe "AM063", on the right side, in the 5th or 4th intercostal space, to obtain the right parasternal short axis view.In conclusions, This study provide normal cardiac dimensions in Arabian horses at rest and showed effect of age, sex, and pregnancy in these dimensions. All dimensional echocardiographic measurements were significantly affected by age, and some of them were significantly affected by sex, but not by pregnancy.